Croatia - Bratičević, Irena (Array, 2013)
Our chapter on Croatia is a part of an anthology of texts in Latin, drawn from classical antiquity to the present, dedicated to Croatian territory and history. The aim is to present Croatia as a part of European Union, on the basis of its cultural inheritance of antiquity as it is written in the Latin language.